(untitled) (International Journal of Engineering and Computer Science, 2013)
A systematic method for deriving three-port converters (TPCs) from the full-bridge converter (FBC) is proposed in this paper. The proposed method splits the two switching legs of the FBC into two switching cells with different sources and allows a dc bias current in the transformer. By using this systematic method, a novel full-bridge TPC (FB-FBC) is developed for renewable power system applications which feature simple topologies and control, a reduced number of devices, and single-stage power conversion between any two of the three ports. The proposed FB-TPC consists of two bidirectional ports and an isolated output port. The primary circuit of the converter functions as a buck-boost converter and provides a power flow path between the ports on the primary side. The FB-TPC can adapt to a wide source voltage range, and tight control over two of the three ports can be achieved while the third port provides the power balance in the system. Furthermore, the energy stored in the leakage inductance of the transformer is utilized to achieve zero-voltage switching for all the primary-side switches. The FB-TPC is analyzed in detail with operational principles, design considerations, and a pulse-width modulation scheme (PWM), which aims to decrease the dc bias of the transformer. Experimental results verify the feasibility and effectiveness of the developed FB-TPC. The topology generation concept is further extended, and some novel TPCs, dual-input, and multiport converters are presented.